Atenção às urgências odontológicas em Unidades de Pronto Atendimento - CARVALHO, Juliane Húngaro de (2021)
The Emergency Dental Service (EDS) has been consolidated as a fundamental member of the oral health care network (OHCN) and its use may reflect the need for adjustments in this network. The retrospective and quantitative descriptive study sought to analyze the profile of EDS care in a medium-sized city and propose strategies for its communication with the OHCN. 10,015 patient records were analyzed, from 2018 to 2019, according to age, gender, neighborhood, region of residence, EDS unit, service shift, and procedures performed. It was found that the age group from 20 to 59 years (80.10%) was the one who most sought the service, with no difference between genders. In the non-commercial shift, 1.06 patients/hour were seen, and in the non-commercial shift, 0.75. The most frequently performed procedures were provisional sealing (34.21%), drug prescription (28.12%), indwelling dressing (16.08%) and coronary opening (12.62%). The EDS and primary care (PC) were fragmented services, which was solved with the use of online spreadsheets and an active search for PC. It is concluded that the economically active age group used the EDS the most, mainly in non-commercial shifts, filling the gap in PC; there was an effective improvement in the integration of the EDS in the OHCN after the implementation of the proposed measures.